Analysis of Operation of a Driving Band Mounting in a Projectile’s Shell - Mieczysław KACZOROWSKI; Zdzisław LINDEMANN; Marek RADOMSKI (Problemy Mechatroniki)
The paper presents computational modelling using the Finite Element Method (FEM) for technological operation of a driving band mounted in a groove of a projectile shell. Exemplary results of analysis for shrapnel cal. 35 mm are given. The analysis showed significant factors influencing the mounting process and a field of residual stresses in a projectile shell. It allowed for determination of mechanical properties of materials of a driving band and a projectile shell as well as of characteristic dimensions of half-finished product of a driving band and a groove in a projectile shell. The obtained investigation results show substantial advantages of such analyses for a design process of new types of gunnery ammunition. Thus, it is possible to optimise the construction and technology, i.e., to minimise the reduced stresses in a field of residual stresses in a projectile shell what limits the possibility of a driving band break (rupture) or cracking a projectile shell inside a barrel during the shot.